(untitled) (Journal of Student Affairs in Africa, 2026)
Relationships constitute a core aspect of psychological wellbeing models. More so, research from different sociocultural contexts has shown that relational experiences provide a form and shape for an individual’s worldview. By applying meaning-making models, this study aimed to explore relational experiences of meaning making that contribute to academic adjustment among African international students at a university in South Africa. In-depth interviews were conducted with 30 undergraduate and postgraduate students. Meaning making through relational experiences among African international students was underscored by their concern for the wellbeing of close family members and in cross-cultural social interactions that imposed a coherent worldview on the students’ lives. Such worldviews provided direction and motivation to forge ahead in their educational pursuits, while acknowledging the importance of intrapersonal connections in this process. Additionally, their social contributions enabled them to establish connections with the broader community. In terms of theoretical contributions, our study showed how relational experiences of meaning making enable international students to forge a sense of identity and purpose, all of which are essential for academic adjustment. Our findings also have implications for wellbeing interventions at higher education institutions.